การศึกษาสภาพและปัญหาการบริหารงานศูนย์การศึกษาพิเศษ - วิรัช ภู่เล็ก (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The purpose of this research was to study the state and problems of the administration of special education centers under the jurisdiction of the Office of Special Education, the Office of basic Education Commission. The population consisted of 39 adinistrators and 130 teachers from 13 special education centers. The instrument used in this research was a questionnaire of which 148 or 87.57 % were completed and returned. The data were analyzed with frequencies and percentage. The findings are described as follows : 1. General Administration, budgeting and planning, documentation and clerical works, personnel, finance and accounting, hardware inventory and building management, public relations, registration and technological information system management were all performed at the high level. Problems found were : inadequacy of budget, non-qualified and incompetent personnel, personnel s work overload, and the lack of updating of the young handicapped information. 2. Educational Promotion and Provision, assistance and consulting services at the initial stage, evaluating and grouping young handicapped, coordination in young handicaped s physical health recovery and readiness, advising and counseling services, co-education with other normal schools, development of network among multi-educational organization for the young handicapped, education operations for private young handicapped, instructional support system, and non-formal and informal education operations were all performed at the high level. Problems found were : inadequacy of personnel and parents cooperation, the lack of budget, the lack of proper tools, and equipment, personnel s work overload, and inadequacy of specialized personnel. 3. Education Improvement, improvement of teaching aids, and educational quality assurance, personnel development, and handicapped network development were all performed at the high level, and lack of educational development research were found. Problems found in this area were the lack of budget and the lack of specialized personnel.